2018
DOI: 10.1590/1806-9282.64.02.154
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the prevalence of vertical hepatitis B transmission in two consecutive generations

Abstract: Introduction: Hepatitis B is an important public health problem in the world and one of the forms of contagion would be through vertical transmission. Precose diagnosis allows the adoption of prophylaxis measures, which results in prevention in more than 90% of cases. Objective: To describe the prevalences of vertical transmission and compare two generations (mother/patient and patient/child). Method: This was a cross-sectional study, which included 101 patients. The interviews were performed through the appli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Contrary to this, the association of isolated HBcAb with HBV DNA may represent a variant of chronic HBV infection with undetectable levels of HBsAg [33]. Many studies reported low infectivity from OBI cases probably due to the low viremia particularly in anti-HBs positive individuals [37][38][39].…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Contrary to this, the association of isolated HBcAb with HBV DNA may represent a variant of chronic HBV infection with undetectable levels of HBsAg [33]. Many studies reported low infectivity from OBI cases probably due to the low viremia particularly in anti-HBs positive individuals [37][38][39].…”
Section: Discussionmentioning
confidence: 94%
“…However, in this study, all the HBsAg carriers were HBeAg negative/HBeAb positive and had low to moderate viral load. Therefore, the probability of perinatal transmission might be low as 10-20% [37].…”
Section: Discussionmentioning
confidence: 99%